Toxic interactions of benzyl alcohol with bacterial endotoxin. - Cebula, T A (1984)
Acute toxic interactions of intravenously administered benzyl alcohol and Escherichia coli O55:B5 (Boivin preparation) endotoxin were examined in rodents. Lethality studies in male CD-1 mice demonstrated that these agents were more toxic when administered in combination than when either was administered alone. Prophylactic treatment with diazepam (5 mg/kg intraperitoneally) protected against lethality induced by either the combination or the endotoxin yet offered little, if any, protection against the lethal effects of benzyl alcohol. Similar treatments with naloxone (5 mg/kg intraperitoneally) failed to protect against either endotoxin-induced or benzyl alcohol-induced lethality, but they significantly protected against the lethal effects of the combination. Although hexobarbital-induced sleeping time was prolonged in endotoxin-treated mice (but was normal in benzyl alcohol-treated mice), a more protracted effect on sleeping time was observed in mice treated with both benzyl alcohol and endotoxin. Moreover, male Wistar rats treated with benzyl alcohol (40 mg) showed no evidence of hepatic lesions, but rats treated in combination with sublethal doses of the alcohol (40 mg) and the endotoxin (0.4 mg) developed hepatic lesions which were severe than those observed in rats treated with endotoxin (0.4 mg) alone. A correlation between altered blood chemistry values and severity of hepatic lesions was demonstrated. These data show in vivo toxic interactions between benzyl alcohol and bacterial endotoxin. In addition, our results indicate that the toxic effects induced by the benzyl alcohol-endotoxin combination are due to an enhancement of the lethal properties of bacterial endotoxin.